Indigenous Cultural Identity of Research Authors Standard: research and reconciliation with Indigenous Peoples in rural health journals - Mark Lock; Faye McMillan; Donald Warne; Bindi Bennett; Jacquie Kidd; Naomi Williams; Jodie Martire; Paul Worley; Peter Hutten-Czapski; Emily Saurman; Veronica Mathews; Emma Walke; et al. (James Cook University, 2022)
The Indigenous Cultural Identity of Research Authors Standard (ICIRAS) is based on a gap in research publishing practice where Indigenous peoples' identity is not systematically and rigorously recognised in rural health research publications. There are widespread reforms, in different research areas, to counter the reputation of scientific research as a vehicle of racism and discrimination. Reflecting on these broader movements, the editorial teams of three rural health journals - Rural and Remote Health, the Australian Journal of Rural Health, and the Canadian Journal of Rural Medicine - adopted a policy of 'Nothing about Indigenous Peoples, without Indigenous Peoples'. This meant changing practices so that Indigenous Peoples' identity could be embedded in authorship credentials - such as in the byline. An environmental scan of literature about the inclusion of Indigenous Peoples in research revealed many ways in which editorial boards of journals could improve their process to signal to readers that Indigenous voices are included in rural health research publication governance. Improving the health and wellbeing of Indigenous peoples worldwide requires high-quality research evidence. This quality benchmark needs to explicitly signal the inclusion of Indigenous authors. The ICIRAS is a call to action for research journals and institutions to rigorously improve research governance and leadership to amplify the cultural identity of Indigenous peoples in rural health research.